2018
DOI: 10.1016/j.jdent.2018.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Resin cements formulated with thio-urethanes can strengthen porcelain and increase bond strength to ceramics

Abstract: The current investigation suggests that it is possible to reinforce the porcelain-RC pair and obtain higher bond strength to LD and ZR with RCs formulated with selected types of thio-urethane oligomers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…The experimental dual-cured resin cement was composed of Bis-phenol A diglycidyl dimethacrylate (Bis-GMA), urethane dimethacrylate (UDMA) and tri-ethylene glycol dimethacrylate (TEGDMA; Esstech) in a 50:30:20 mass ratio (BisGMA-UDMA-TEGDMA materials). This monomer system was chosen based on a previous study [33] which showed enhanced bonding to ceramics compared to other resins. All monomers were purchased from Esstech (Essington, PA, USA).…”
Section: Experimental Resin Cementmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental dual-cured resin cement was composed of Bis-phenol A diglycidyl dimethacrylate (Bis-GMA), urethane dimethacrylate (UDMA) and tri-ethylene glycol dimethacrylate (TEGDMA; Esstech) in a 50:30:20 mass ratio (BisGMA-UDMA-TEGDMA materials). This monomer system was chosen based on a previous study [33] which showed enhanced bonding to ceramics compared to other resins. All monomers were purchased from Esstech (Essington, PA, USA).…”
Section: Experimental Resin Cementmentioning
confidence: 99%
“…Thio-urethane oligomers were added to the methacrylate organic matrix in proportions of 0 or 20 wt%. This proportion has been demonstrated to provide increased mechanical properties without affecting the material's viscosity [33]. The cement without the thiourethane served as an experimental control (EC).…”
Section: Experimental Resin Cementmentioning
confidence: 99%
“…Six TU oligomers were synthesized as described previously . Information about the oligomers used in the study is presented in Table .…”
Section: Methodsmentioning
confidence: 99%
“…Guazzato et al [38] related two stress concentration peaks during flexural testing for bilayer systems, both on the bottom surface of the core and the porcelain when the specimens were tested with the porcelain turning down (tensile side). Thus, the transformation toughening mechanism may have generated a slight decrease in the zirconia's deflection during the flexural fatigue test, thereby generating lower stress concentration at the bottom surface of the porcelain [46], which did not happen for the liner application group. Furthermore, the surface topography analysis showed that the liner application leads to the presence of pores and high surface irregularities near the interface which could contribute to the mechanism of crack propagation, as the pores are small in dimension and may have had problems to be filled by the porcelain layer (Fig.…”
Section: Groupsmentioning
confidence: 99%